What does Brexit Tell Us about Our Understanding of European Identity?. Issue 3 (13th August 2019) - Leith, Murray Stewart; Sim, Duncan; van der Zwet, Arno; Boyle, Elizabeth
Abstract: This paper reports on a number of Eurobarometer surveys undertaken by the European Commission as a way of reflecting on Brexit and the challenges it poses to European identity. Our work with the surveys has been undertaken in the context of developing an educational game (RU EU?) which will explore European identity. European citizenship and identity have been strongly promoted by the EU but, while they appear to have been accepted at an elite level, the EU—and the UK in particular—have so far not constructed a narrative which has been supported by 'ordinary' citizens. Brexit has therefore exposed the failings of European elites in this regard. That said, there is some evidence that the complexities of Brexit have led to a strengthening of European identity in the other EU 27 countries.